Messenger RNA for an antigen-specific binding molecule from an antigen-specific T-cell hybrid. - Beaman, K D (1984)
The T-cell hybridoma 51H7D specifically binds the hapten azobenzenearsonate (ABA). An antiserum (anti-PCIF) specific for antigenic determinants shared by antigen-binding molecules of T cells (TABM) was used to precipitate polyribosomes containing mRNA for TABM from this T-cell hybridoma. The resultant mRNA was translated in vitro. The translated product (TrP51H7D) bound specifically ABA and was bound by both anti-PCIF and anti-T-cell suppressor factor. The parent lymphoma BW5147 yielded a similar translated product with the same antiserum used to isolate specific mRNA containing polysomes. This product (TrPBW) was bound by the antiserum used but did not bind ABA. The specific translated protein from both cells had a pI of approximately equal to 5.0, and apparent molecular weight of 71,000 (reduced) or 145,000 (nonreduced). Both protein products, when treated with guanidine to break down all noncovalent bonds, revealed an elemental peptide of Mr 23,500. The cDNA made from the isolated mRNA had 600-900 bases. mRNA of this size is expected for a protein of Mr 25,000. Our data indicate that a TABM specific for ABA is composed of peptides of Mr 23,500.